Main components of business cards design - Романенкова, Ю. В. (Proceedings of National Aviation University (archive), 2003)
The essay is dedicated to the urgent problem of necessity of creation of professional design of business cards, that are important part of the image of modem businessman. There are classification of cards by functional principle, the functions of cards of each type were analyzed. All components of business card, variants of its composition schemes, color characteristics, principles of use of trade marks and other design elements have been allocated